(untitled) (Agricultural Engineering, 2023)
This paper proposes a new biostimulant coating for soybean seeds. The aim of the study was to create a coating for Glycine max (L.) Merr. soybean seeds, using root infusion from Arctium lappa L. as a biostimulant component. The effectiveness of the produced coating was evaluated in a three-year field study. The analysis of the effectiveness of the developed coating was based on the evaluation of plant biometric traits and yield. The study showed that the designed and manufactured soybean seed coating based on the root infusion of Arctium lappa L. can be considered as a new agronomic strategy to improve the productivity of soybean Glicyne max (L.) Merr. under actual field conditions. The application of the biostimulant coating resulted in soybean plants with significantly increased biometric traits (plant height, height of the first pod set, number of pods per plant, number of seeds per pod) and productivity (yield improvement of more than 10%). Only a reduced weight of 1,000 seeds compared to control samples was noted.